The implementation of project-based learning in high school mathematics - Nugrahani, Permata; Sunardi; Sukmawati, Fatma (Proceedings of International Conference on Research in Education, 2025)
This study aims to discuss the implementation of mathematics learning at Pangudi Luhur St. Yosef Surakarta High School on the topic of Systems of Linear Equations in Three Variables using the Project-Based Learning (PjBL) model. This study employs a descriptive qualitative approach, using 158 tenth-grade students as subjects. Data were obtained through classroom observation, interviews, and document analysis, including lesson plans, project worksheets, and student work. The results of this study indicate that the mathematics learning process using the Project-Based Learning (PjBL) model is still procedural and lacks connection to real-world contexts. Students tend to imitate the teacher’s examples, so the process of exploring ideas, reflecting, and solving problems creatively is not yet optimal. Therefore, students’ mathematical creative thinking skills have not developed, and it is necessary to incorporate real-world contexts and reflection at each stage of the project to make mathematics learning more meaningful, mindful, and joyful.